2022
DOI: 10.1002/anie.202202061
|View full text |Cite
|
Sign up to set email alerts
|

Selective Coupling of 1,2‐Bis‐Boronic Esters at the more Substituted Site through Visible‐Light Activation of Electron Donor–Acceptor Complexes

Abstract: 1,2‐Bis‐boronic esters are useful synthetic intermediates particularly as the two boronic esters can be selectively functionalized. Usually, the less hindered primary boronic ester reacts, but herein, we report a coupling reaction that enables the reversal of this selectivity. This is achieved through the formation of a boronate complex with an electron‐rich aryllithium which, in the presence of an electron‐deficient aryl nitrile, leads to the formation of an electron donor–acceptor complex. Following visible‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 69 publications
2
21
0
Order By: Relevance
“…β-Aryl-substituted alkenyl boronates were then investigated, and the hydrosilylation products were formed with exclusive α-selectivity (33-46, 41-81% yields), regardless of electron-withdrawing or electron-donating groups on the aryl substituent. Some sensitive functionalities in transition-metal catalyzed hydrosilylation or hydroborylation, including aryl chlorides (41) and aryl bromides (44) were well-tolerated with our protocol.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…β-Aryl-substituted alkenyl boronates were then investigated, and the hydrosilylation products were formed with exclusive α-selectivity (33-46, 41-81% yields), regardless of electron-withdrawing or electron-donating groups on the aryl substituent. Some sensitive functionalities in transition-metal catalyzed hydrosilylation or hydroborylation, including aryl chlorides (41) and aryl bromides (44) were well-tolerated with our protocol.…”
Section: Resultsmentioning
confidence: 98%
“…The extremely low reactivity of isopropenylboronic acid pinacol ester (29) suggests that a completely different strategy is required to synthesize vicinal borosilanes. We were inspired by the studies on 1,2-boron radical migration [42][43][44][45][46] and found that the switch of alkene substrates to α-substituted allyl boronates readily delivered vicinal borosilanes (Table 2). This strategy worked well for α,α-dialkyl-substituted allyl boronates (63-69, 52-84% yields), and the presence of a methyl group at the γ position was tolerated (69).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the Aggarwal group had reported the photoinduced coupling of 1,2-bis-boronic esters with aryl nitriles, aryl halides or electron-de cient alkenes, providing the β-tertiary and quaternary boronic ester products through a radical 1,2-boron shift process. [69][70][71] The Liu group had developed a visible-light-induced alkynylation of 1,2-bis-boronic esters with 4CzIPN as the organic photocatalyst to achieve the corresponding β-branched organoboron. 72 Despite important progress have been made, present methods for the synthesis of β-branched organoboron often suffer from poor substrate scope, elusive regioselectivity and/or multi-step synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the hypervalent thiophenative aryl salts provided the possibility for photochemical reactions. In recent years, electron donor–acceptor (EDA) complex activation through photocatalysis has been demonstrated for radical transformations. Procter reported one such route using a catalytic amount of triphenylamine as an effective EDA donor for thiophenative aryl salt activation. Also, Molander disclosed that sulfides and thioether could act as effective electron donors to form an EDA complex with thianthrenium salts that allow the reaction to take place under irradiation.…”
mentioning
confidence: 99%